Fritz Meier, Nachgelassene Schriften, Band 1. Bemerkungen zur Mohammedverehrung, Teil 1. Die Segenssprechung über Mohammed - Schubert, Gudrun (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
The centre of Islamic piety is the Prophet Mohammed whose perfection was eternal from pre-existence and who stands completely within God's grace. For the believers he occupies the most important role of intermediary between themselves and God. The Prophet's intercession is accepted, and through his intercession the believers hope their prayers will be heard and their wishes fulfilled. Invoking blessings on Mohammed is a means for attaining the effective help of the Prophet. Along with expressing thanks for the benefits mankind has received from Mohammed, it constitutes a preliminary to the intercession one hopes for from the Prophet. Fritz Meier, in part one of his Bemerkungen zur Mohammedverehrung Observations on the Veneration of the Prophet , has written a monograph about the tasliya which surveys the use and meaning of invoking blessings on the Prophet in the life of a Muslim.